Enhancing tailings revegetation using shallow cover systems in arid environments: Hydrogeochemical, nutritional, and ecophysiological constraints. (28th May 2018) - Robson, Thomas; Golos, Peter J.; Stevens, Jason; Reid, Nathan
Abstract: Mineral tailings impoundments represent a rapidly growing land area requiring revegetation and a major challenge to restoring biodiversity in postmined environments. Topsoil covers are essential for revegetation, to mitigate the physical and hydrogeochemical obstacles presented by tailings. However, mines in arid and semiarid regions are often large scale and geographically isolated from resources and suffer a scarcity of suitable topsoil, stimulating interest in cost‐effective shallow cover systems incorporating minimal volumes of local material. Using a mine in arid Western Australia as a case‐study, we address challenges pertinent to using 200‐mm‐deep sandy topsoil directly overlying mildly reactive, circum‐neutral copper ore tailings. We combined detailed hydrogeochemical, ecophysiological, and nutritional data from a year‐long glasshouse experiment, to evaluate responses of native species to the model system. The model system enhanced emergence, growth, and root development by providing a physical and hydrogeochemical buffer, increasing the volume of profile with conditions favourable to water and nutrient acquisition. Plants scarcely utilised saline water from the underlying tailings, limiting growth between irrigation events, although the tailings did support minimal functional activity over timescales in the order of weeks. We identified relatively high tailings pore‐water salinity, the limited volume of geochemically benign topsoil providing storage release of uncontaminated meteoric water, and the geochemically evolving nature of the tailings cover system, as key challenges to overcome. The findings encourage further studies incorporating optimised designs and demonstrate the benefits of combining detailed, temporally resolved hydrogeochemical and ecophysiological data to adequately capture the plant–water relations existing within candidate cover systems.